An operational definition of prior criminal record - Nelson, James F. (Journal of quantitative criminology, 1989)
A variety of measures of prior criminal record is used to explain differences in incarceration for defendants arrested in New York State. The analysis suggests that (1) measures based upon arrest, conviction, or incarceration data are equally effective at explaining differences in incarceration percentages; (2) measures based upon counts do better in their logarithmic than in their arithmetic scales; (3) prior record is more closely related to incarceration for moderately serious than for serious or minor crimes; and (4) prior record is more closely related to incarceration for crimes that have a theft component than for crimes that do not. A composite prior record measure is developed that combines arrest and conviction data. It is easy to compute, yet it is as effective at explaining variation in incarceration as the most elaborate measures examined.